Reduced/No Dexamethasone With Netupitant/Palonosetron and Olanzapine for Chemotherapy‑Induced Nausea/Vomiting in Highly Emetogenic Chemotherapy: Phase III Noninferiority Trial - Yanchun Meng; Yingying Liu; Mingxi Lin; Lili Wang; Yuxin Mu; Ling Yang; Yiqun Du; Xiaojun Liu; Yong Chen; Shaodong Tian; Qin Zhou; Xiaojie Zhuang; et al. (Journal of Clinical Oncology, 2026)
PURPOSE Guideline-recommended 4-day dexamethasone (DEX) for highly emetogenic chemotherapy (HEC) raises toxicity and immunotherapy interference concerns. We tested whether DEX reduction or omission with netupitant/palonosetron (NEPA) plus olanzapine (OLZ) is noninferior to standard DEX. PATIENTS AND METHODS In this open-label, randomized phase III noninferiority trial across 28 Chinese centers, adults receiving HEC received NEPA (day 1) plus OLZ (days 1-4) and were randomly assigned to standard DEX (12 mg day 1, 8 mg days 2-4), DEX-sparing (6 mg day 1 only), or DEX-free (no DEX). The primary end point was complete response (CR; no emesis/no rescue medication) from 0 to 120 h. Noninferiority margin was –12% (one-sided α = .025). RESULTS Of 644 randomly assigned patients (median age 54.9 years; 66.0% female), stratified analysis showed overall CR rates of 72.4% for standard, 72.2% for DEX-sparing (stratified risk difference [RD], –0.2% [95% CI, –8.7 to 8.5]; P noninferiority = .005), and 70.1% for DEX-free (stratified RD, –2.2% [95% CI, –10.7 to 6.4]; P noninferiority = .014). Both met noninferiority, confirmed in per-protocol analysis. Steroid-related toxicities were significantly lower with DEX-sparing and DEX-free regimens versus standard. CONCLUSION NEPA plus OLZ with reduced (6 mg day 1 only) or no DEX is noninferior to standard 4-day DEX for chemotherapy-induced nausea and vomiting prevention in HEC, supporting steroid-sparing strategies particularly relevant in the chemo-immunotherapy era.